2012
DOI: 10.1016/j.brainres.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol protects against hippocampal damage and impairments in fear conditioning resulting from transient global ischemia in mice

Abstract: Estradiol protects against hippocampal damage and some learning impairments resulting from transient global ischemia in rats. Here, we seek to validate a mouse model of transient global ischemia and evaluate the effects of estradiol on ischemia-induced hippocampal damage and behavioral impairments. Female C57Bl6/J mice were ovariectomized and implanted with estradiol-or oil-secreting capsules. One week later, mice experienced 15-min of 2-vessel occlusion (2-VO) or sham surgical procedures. Five days later, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…However, estrogen treatment before and after ischemia-reperfusion following ovariectomy was seen to markedly restore the impairment to the BBB. In the same vein, previous studies demonstrated that estrogen treatment played a protective role against the hippocampus damage inflicted during global ischemia, and this result lends support to ours (4,12).…”
Section: Discussionsupporting
confidence: 77%
“…However, estrogen treatment before and after ischemia-reperfusion following ovariectomy was seen to markedly restore the impairment to the BBB. In the same vein, previous studies demonstrated that estrogen treatment played a protective role against the hippocampus damage inflicted during global ischemia, and this result lends support to ours (4,12).…”
Section: Discussionsupporting
confidence: 77%
“…Although, MMPs act as proinflammatory factor, they are also important for normal physiological function such as neuronal regeneration, cell proliferation, angiogenesis, and apoptosis (51). In addition, in our study previous TIA was related to cytokines downregulation implicated in molecular functions and biological processes previously described in the preconditioning phenomena like heat shock proteins (6,52), receptor of protein tyrosine kinase activity (53,54), and the response to estradiol (55).…”
Section: Discussionsupporting
confidence: 55%
“…E2-treated ovariectomized female rats performed the eye-blink test better than vehicle-treated ovariectomized rats during EW (our unpublished observation). E2 treatment significantly improved Rotarod performance of ischemic rats [59], suggesting that E2 exerts a protective role in cerebellar neurons.…”
Section: Discussionmentioning
confidence: 99%